The role of courts in a democracy: alternatives to judicial supremacy - Parau, C (2011)
This policy brief assesses the adoption of US models of judicial activism in post-Communist countries of central and Eastern Europe, and proposes an alternative model in the form of co-equality as a more effective way to reconcile popular sovereignty with individual liberty.